EFEKTIVITAS PENGGUNAAN TEKNIK PEMBELAJARAN PETA PIKIRAN (MINDMAPPING) TERHADAP KEMAMPUAN MENULIS TEKS NARASI SISWA SD - Septiarifa Salsabila; Alfauzan Mhd Rozak; M. Habibi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This research was conducted to examine the effectiveness of the mind mapping learning technique in enhancing the narrative writing abilities of elementary school students. The study used a Systematic Literature Review (SLR) approach by analyzing various relevant scientific articles published from 2014 to 2026. Data were collected through searches on Google Scholar and other academic journals using the keywords mind mapping, narrative writing, and elementary school. The process of selecting articles followed the PRISMA stages, namely identification, screening, eligibility, and inclusion. The results of the selection process showed that several articles met the inclusion criteria and were further analyzed in this study. The findings demonstrated that the application of the mind mapping technique positively contributed to the improvement of elementary school students’ narrative writing skills. This technique assists students in organizing and developing ideas systematically, enabling them to structure story plots, identify main ideas, and connect ideas in narrative texts more effectively. Furthermore, the use of mind mapping was found to increase students’ creativity, motivation, imagination, and active involvement during classroom learning activities. Several studies also reported improvements in student achievement, indicated by higher average scores, posttest outcomes, and significant hypothesis testing results after the implementation of the mind mapping technique. Therefore, the mind mapping learning technique can be considered an effective alternative instructional method for improving narrative writing skills among elementary school students.